Patterned tungsten disulfide/graphene heterostructures for efficient multifunctional optoelectronic devices. Issue 9 (14th February 2018) - Rossi, A.; Spirito, D.; Bianco, F.; Forti, S.; Fabbri, F.; Büch, H.; Tredicucci, A.; Krahne, R.; Coletti, C.
Abstract : A patterned-growth, scalable fabrication strategy allows photodetectors with good electrical properties that show fast response with red light and persistent photocurrent with blue light. Abstract : One of the major issues in graphene-based optoelectronics is to scale-up high-performing devices. In this work, we report an original approach for the fabrication of efficient optoelectronic devices from scalable tungsten disulfide (WS2 )/graphene heterostructures. Our approach allows for the patterned growth of WS2 on graphene and facilitates the realization of ohmic contacts. Photodetectors fabricated with WS2 on epitaxial graphene on silicon carbide (SiC) present, when illuminated with red light, a maximum responsivity R ∼220 A W −1, a detectivity D * ∼2.0 × 10 9 Jones and a −3 dB bandwidth of 250 Hz. The retrieved detectivity is 3 orders of magnitude higher than that obtained with graphene-only devices at the same wavelength. For shorter illumination wavelengths we observe a persistent photocurrent with a nearly complete charge retention, which originates from deep trap levels in the SiC substrate. This work ultimately demonstrates that WS2 /graphene optoelectronic devices with promising performances can be obtained in a scalable manner. Furthermore, by combining wavelength-selective memory, enhanced responsivity and fast detection, this system is of interest for the implementation of 2d-based data storage devices.